2020
DOI: 10.3389/fvets.2020.583342
|View full text |Cite
|
Sign up to set email alerts
|

Bladder and Bowel Management in Dogs With Spinal Cord Injury

Abstract: Spinal cord injury in companion dogs can lead to urinary and fecal incontinence or retention, depending on the severity, and localization of the lesion along the canine nervous system. The bladder and gastrointestinal dysfunction caused by lesions of the autonomic system can be difficult to recognize, interpret and are easily overlooked. Nevertheless, it is crucial to maintain a high degree of awareness of the impact of micturition and defecation disturbances on the animal's condition, welfare and on the owner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 103 publications
2
18
0
Order By: Relevance
“…This study indicated that urinary and fecal incontinence was present in a high percentage of dogs with DM, which was similar to what was noted in patients with ALS [19]. The regulation of urination and defecation involves a complex neural control system in the brain, spinal cord, and peripheral autonomic neurons [20]. In dogs with DM, spinal cord lesions spread in ascending and descending orders from the caudal thoracic spinal cord [21], leading to the development of urinary and fecal incontinence.…”
Section: Discussionsupporting
confidence: 81%
“…This study indicated that urinary and fecal incontinence was present in a high percentage of dogs with DM, which was similar to what was noted in patients with ALS [19]. The regulation of urination and defecation involves a complex neural control system in the brain, spinal cord, and peripheral autonomic neurons [20]. In dogs with DM, spinal cord lesions spread in ascending and descending orders from the caudal thoracic spinal cord [21], leading to the development of urinary and fecal incontinence.…”
Section: Discussionsupporting
confidence: 81%
“…This was documented in three cases, however only two of those were presumed to be secondary to the cranial thoracic myelopathy, which were still ambulatory despite the urinary/faecal incontinence. A myelopathy in the area of interest of our study, from T1 to T6, could cause a supra-sacral (cranial to the L7 spinal cord segment) incontinence ( 55 ). This can occur due to the damage of the upper motor neuron pathways to the bladder and rectum, resulting in a retention urinary incontinence, due to increased sphincter tone, and faecal incontinence due to the inability to control defecation once the defecation reflex has been triggered ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current approaches for dogs with acute thoracolumbar myelopathy due to compressive IVD extrusion have been recently reviewed 19–21 . Clinical examination (including testing nociception, which is a key factor in several reported grading systems) is critical in prognostication, where a loss of nociception indicates a worse prognosis for recovery than intact nociception.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,15 The current approaches for dogs with acute thoracolumbar myelopathy due to compressive IVD extrusion have been recently reviewed. [19][20][21] Clinical examination (including testing nociception, which is a key factor in several reported grading systems) is critical in prognostication, where a loss of nociception indicates a worse prognosis for recovery than intact nociception. MRI is the preferred diagnostic modality, and, after localization of the compressive lesion, surgery is often (and, most will consent, preferably) performed shortly after.…”
Section: Discussionmentioning
confidence: 99%